Cross-country analysis of life cycle assessment–based greenhouse gas emissions for automotive parts: Evaluation of coefficient of country. (March 2021) - Akhshik, M.; Panthapulakkal, S.; Tjong, J.; Bilton, A.; Singh, C.V.; Sain, M.
Abstract: Life cycle assessments (LCAs) are time consuming and can be expensive. Sometimes a company simply needs to have a basic estimate of the environmental impacts of the country which they are conducting the operations. If a company plans to move a current established production line or set up a new production line, which countries should be considered for a full LCA? It would be useful to have a coefficient for each country which could scale an established LCA result to estimate each new country's emissions. The following study develops country coefficients which could be used to scale LCA results. After careful study of many environmental parameters, two were selected to develop the country coefficient: total primary energy supply and electricity grid mix. This coefficient was designed for fiber-reinforced composites; and as the sources of natural fiber could be very different; we also included forestry and agriculture in our study. At the end of the study, we performed LCA-based greenhouse gas emission estimates for several countries and compared the results to the estimates using the country coefficients. We were able to reach an impressive result of up to 95% accuracy in comparison to the full LCA In just simple steps. Highlights: A conversion Coefficient for greenhouse gas emissions from a country to another. Comparison of countries for the production of the plastic automotive parts. Greenhous gas conversion analysis of fiber reinforced composite automotive parts.